2012
DOI: 10.1158/1535-7163.mct-12-0098
|View full text |Cite
|
Sign up to set email alerts
|

Cotargeting MAPK and PI3K Signaling with Concurrent Radiotherapy as a Strategy for the Treatment of Pancreatic Cancer

Abstract: There is an urgent need for the development of novel therapies to treat pancreatic cancer, which is among the most lethal of all cancers. KRAS activating mutations, which are found in >90% of pancreatic adenocarcinomas, drive tumor dependency on the Ras/MAPK and Akt signaling pathways. Radiation is currently being explored as a component of the standard treatment regimen for pancreatic cancer. This study’s purpose was to test the hypothesis that MEK inhibitors will offer clear therapeutic benefit when integrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 32 publications
5
65
0
Order By: Relevance
“…Immunoblotting was performed as described before (28). Briefly, cell lysates were prepared in RIPA lysis buffer (1% NP-40, 150mM NaCl, 50mM Tris-HCL pH 7.4, 0.25% Na-deoxycholate, 1 mM EDTA) supplemented with 1× protease inhibitor (Complete, Roche Applied Science) and phosphatase inhibitors (PhosSTOP, Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoblotting was performed as described before (28). Briefly, cell lysates were prepared in RIPA lysis buffer (1% NP-40, 150mM NaCl, 50mM Tris-HCL pH 7.4, 0.25% Na-deoxycholate, 1 mM EDTA) supplemented with 1× protease inhibitor (Complete, Roche Applied Science) and phosphatase inhibitors (PhosSTOP, Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
“…(28) Briefly, cells were plated in 6 well dishes, and treated with or without 10ng/ml nab-paclitaxel. After 48 hours of treatment, the percentage of apoptotic cells was determined using ApoDETECT™ Annexin V-FITC kit (Invitrogen) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many in vitro and in vivo studies have shown synergistic outcomes in tumor cell death by simultaneous inhibition of these two pathways. 810 As the Ras/MEK/ERK and PI3K/Akt/mTor pathways are regulated by different mechanisms, simultaneous co-targeting of these pathways is an attractive anticancer strategy. Current approaches toward multikinase drug targeting involve drug administration as either (a) two or more therapeutics (drug cocktail) or (b) a polyfunctional multitargeting single agent therapeutic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ~40% of patients with GBM have an amplified EGFR gene which results in constitutive activation of AKT and ERK (10). AKT and ERK signaling pathways play vital roles in regulating many fundamental cellular processes and they are associated with resistance to treatment in GBM cells (11,12). β-elemene, a Chinese antitumor medicine extracted from the plant Curcuma wenyujin, has been isolated as a monomeric drug and has a broad-spectrum antitumor effect in various tumor cells, such as lung (13), breast carcinoma (14), leukemia (15), ovarian cancer (16) and GBM (17).…”
Section: Introductionmentioning
confidence: 99%